Food Insecurity and Substance Use in People with HIV Infection and Substance Use Disorder - Raja, Akila (Subst Abus, 2022)
BACKGROUND: Food insecurity and substance use are common among people living with HIV (PLWH). Substance use may help people cope with hunger and thus be associated with food insecurity, but the association is uncertain. This study assessed whether, in PLWH and substance dependence, if there was an association between food insecurity and substance use. METHODS: We studied adults with HIV and current substance dependence or ever injection drug use interviewed at 12 and 24 months after enrollment in a prospective cohort study. The presence of food insecurity (insufficient food quantity or quality, or anxiety about its availability) was assessed using the Household Food Insecurity Assessment Scale questionnaire (HFIAS). Unhealthy alcohol use was assessed with the Alcohol Use Disorder Identification Test – Consumption (AUDIT-C) and past 30-day other drug use with the Addiction Severity Index. Associations using repeat cross-sectional data from each of two time-points, 12 months apart, from the same participants were tested using generalized estimating equations logistic regressions. RESULTS: The 233 participants had a mean age of 50 years and 65% were male. At the first interview, 44% reported food insecurity, 40% unhealthy alcohol use, 25% past 30-day cocaine use, and 17% past 30-day illicit opioid use. In analyses adjusted for demographics, social factors, physical and mental health function, and substance use related variables, there was no significant association between food insecurity and unhealthy alcohol use (adjusted odds ratio (aOR)=1.06 (95% CI: 0.59, 1.87)). Those with food insecurity had higher odds of illicit opioid use (aOR = 2.5 (95% CI: 1.12, 5.58)) and cocaine use (aOR = 1.95 (CI 95%: 1.00, 3.81)). CONCLUSION: Food insecurity was not associated with unhealthy alcohol use but was associated with cocaine and illicit opioid use. Given the prevalence and impact substance use has on PLWH, food insecurity should be identified and addressed.